2015
DOI: 10.1111/ahe.12174
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Coronary Ostia in Domestic Shorthair Cat

Abstract: Diagnosis and treatment of heart diseases due to changes in the coronary vascularization need a detailed knowledge on the morphology and possible variations of the aortic valves and coronary ostia. This study was performed to clarify details on morphology of these structures in domestic cats. The tricuspid aortic valve was examined in 65 domestic shorthair cats. The location of coronary ostia was determined either inferior to (26 and 20%, left and right coronary ostium - LCO and RCO), at (65 and 66%) or superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 20 publications
5
26
0
Order By: Relevance
“…They are also a known entity in humans but having only little clinical significance (Angelini 1989). In our study, the proportion of lynx with an accessory coronary orifice or other variation of its formation was similar to that of domestic cats, 19% and 20%, respectively (Barszcz et al 2016). In domestic cats, additional ostia were most commonly found in conjunction with the right coronary ostia, whereas in the present study they were located in the left.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…They are also a known entity in humans but having only little clinical significance (Angelini 1989). In our study, the proportion of lynx with an accessory coronary orifice or other variation of its formation was similar to that of domestic cats, 19% and 20%, respectively (Barszcz et al 2016). In domestic cats, additional ostia were most commonly found in conjunction with the right coronary ostia, whereas in the present study they were located in the left.…”
Section: Discussionsupporting
confidence: 71%
“…However, excessive diffuse networks of ventricular bands have been associated with heart failure and death in cats (Liu et al 1982;Robinson and Robinson 2015). The presence of accessory coronary orifices has been reported in other mammalian species, including the domestic, shorthair cat (Barszcz et al 2016) and the Syrian hamster (Durán et al 2007). They are also a known entity in humans but having only little clinical significance (Angelini 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were a stronger paraconal interventricular branch and a weaker circumflex branch. This type of trunk morphology has also been described in ruminants (Nickel et al 1981;Barone 1996), roe deer (Frąckowiak et al 2007), Bactrian camel (Yuan et al 2009), donkey (Ozgel et al 2004), porcupine (Atalar et al 2003), ringed seal (Smodlaka et al 2008), chinchilla (Ozdemir et al 2008), cat (Barszcz et al 2014(Barszcz et al , 2016b and European bison (Kupczyńska et al 2015). Whereas Bahar et al (2007) reported that in the Angora rabbit, the common trunk of the left coronary artery was divided into the paraconal interventricular branch, the circumflex branch and the proximal branch of the left atrium.…”
Section: Discussionmentioning
confidence: 71%
“…Descriptions of the morphology of individual sections of the aorta have been featured in numerous veterinarian publications (3,4,8,9,17,18,21,26,29). In domestic mammals two types of direct branches of the aortic arch can be distinguished.…”
Section: Resultsmentioning
confidence: 99%